2023
DOI: 10.1001/jamanetworkopen.2022.50960
|View full text |Cite
|
Sign up to set email alerts
|

Economic Burden of the 2020 COVID-19 Hospitalizations in Spain

Abstract: This economic evaluation reports the total and per patient costs of inpatient care for COVID-19 in Spain in 2020.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 5 publications
0
6
1
Order By: Relevance
“…A total of 14,742 patients were admitted with asymptomatic COVID-19 in Spanish hospitals ( Table 1 ) and 217,106 patients admitted with a primary diagnosis of COVID-19 ( 6 ). Asymptomatic cases represent 6.35% of all COVID-19 hospitalized patients in 2020.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 14,742 patients were admitted with asymptomatic COVID-19 in Spanish hospitals ( Table 1 ) and 217,106 patients admitted with a primary diagnosis of COVID-19 ( 6 ). Asymptomatic cases represent 6.35% of all COVID-19 hospitalized patients in 2020.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have assessed the direct costs of symptomatic COVID-19 in different contexts ( 6 , 19 , 20 ). However, economic information on asymptomatic COVID-19 is scarce.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 The pandemic has far-fetched consequences in terms of its indirect effects due to morbidity and mortality. 2 Economic burden associated with COVID-19 has been estimated across various countries around the globe, such as Africa, 42 China, 39 India, 10 Iran, 43 Russia, 44 Spain, 45 Switzerland, 46 USA 47 and Vienna. 48 As per US estimates, GDP loss associated with COVID-19 would amount to a cumulative US$1.4 trillion by 2030.…”
Section: Discussionmentioning
confidence: 99%
“…A French study reported cost per patient according to three levels of care: no or low-flow oxygen support (level 1: €3,989), non-invasive ventilation (level 2: €10,577), and mechanical ventilation (level 3: €21,133) (6). Another European study reported similar cost results although using different severity criteria: general hospitalization was €4,122.96 while intensive care unit (ICU) admission was €21,199.20 (7). In Latin America a Brazilian study reported a mean cost of US$7,394 for general hospitalization and US$12,179 for ICU admission (8).…”
Section: Introductionmentioning
confidence: 99%